2015
DOI: 10.1016/j.urology.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Presence of Sperm in the Vasal Fluid During Vasectomy Reversal and Postoperative Patency: A Systematic Review and Meta-analysis

Abstract: Objective To investigate the association between the presence of sperm in the vasal fluid during vasectomy reversal (VR) and postoperative patency. Methods We performed a systematic review and meta-analysis of the English-language literature reporting on the association between the presence of sperm in the intraoperative vasal fluid (i.e., whole/parts versus none) and patency (i.e., patent or not) after microsurgical vasovasostomy (VV) for men with obstructive azoospermia due to vasectomy. Odds ratios (OR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Specifically, we showed that the odds of postoperative patency were approximately 14 times higher given the presence of intravasal whole spermatozoa as opposed to merely having sperm fragments or azoospermia. These odds, while not directly comparable to the 49 odds we identified in the recent meta-analysis due to a difference in the way the independent variable was modeled, are in agreement with our meta-analysis (Scovell et al, 2014). Given the heterogeneity of the studies included in the meta-analysis, it is a challenge to compare OR from the meta-analysis to the OR in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Specifically, we showed that the odds of postoperative patency were approximately 14 times higher given the presence of intravasal whole spermatozoa as opposed to merely having sperm fragments or azoospermia. These odds, while not directly comparable to the 49 odds we identified in the recent meta-analysis due to a difference in the way the independent variable was modeled, are in agreement with our meta-analysis (Scovell et al, 2014). Given the heterogeneity of the studies included in the meta-analysis, it is a challenge to compare OR from the meta-analysis to the OR in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Other factors that appeared to influence post-operative success were the gross quality of the vasal fluid and the presence of spermatozoa or sperm fragments at the time of vasectomy reversal (VR). We recently published a meta-analysis demonstrating that the odds of post-operative patency were approximately four times higher given the presence of intravasal spermatozoa or sperm fragments as opposed to their absence (Scovell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…During the operation, the surgeon's decision to proceed with a VV rather than with a VE depends on the gross fluid quality that is expressed from the testicular end of the vas deferens and the microscopic examination of the fluid. In a systematic review and meta‐analysis of the reports on the association between the presence of sperm in the intraoperative vasal fluid and patency, it was reported that the odds ratio of postoperative patency was 4.1‐fold higher in the presence of intravasal sperm or sperm parts than in their absence . Another study confirmed the association between the presence of intravasal spermatozoa during a VV and having a successful patency outcome in a large series from 2 experienced surgeons (n = 1331) .…”
Section: Predictors Of Postoperative Patency and Pregnancymentioning
confidence: 85%
“…However, because microscopic examination of the vasal fluid is not universally performed, certainly some of the failures with a VV might have occurred in patients who actually required a VE because of epididymal obstruction. Of course, performing a VE rather than a VV is an intraoperative decision and it remains difficult to determine before surgery which patients will have epididymal obstruction and will require a VE …”
Section: Predictors Of Postoperative Patency and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation